La Memoria Nacional y la Voluntad Humana en la novela «Entre naranjos» de Vicente Blasco Ibanez (Un estudio analítico) - محمدهلالسليم م.دقاسم (Al-Adab Journal, 2018)
In this research we discussed the subject of memory , in all its forms which related with national identity and belonging of Spanish society in the nineteenth century , through novel (Among the Trees of Orange) of Spanish writer Blasco Ibanez , when human’s life and his style and way of living attached to the place he grew up and influenced by the environment where he lived , influenced by the traditions and religious values and morals , they become a part of his personality and his style , even if he changed his place or lived in another country , moreover we discussed the memory of body, which is the feelings and emotions of human, when all the moments of love , happiness and pain linked to the places where he lived , these form the memory in humans also shows belonging .